Participação de receptores TRPV1 nas respostas defensivas mediadas pela substância cinzenta periaquedutal dorsolateral de ratos - Ana Flavia Santos Almeida (2011)
The behavioral responses of fear and anxiety results from the expression of emotions arising from the animal reactions in the face of aversive stimuli they present a danger or threat to survival. Such responses are related to the release of neurotransmitters present in key brain structures of the system of defense, as the dorsolateral periaqueductal gray (dlPAG). Several studies suggest that glutamatergic neurotransmission facilitates aversive reactions. Additionally, several other neurotransmitter systems present in dlPAG might modulate these responses, as endovanilloid and endocannabinoid systems. Activation of vanilloid receptor type 1 (TRPV1) facilitates glutamatergic synaptictransmission in dlPAG, but its role on the modulation of defensive responses was unclear. Moreover, studies have been shown that the cannabinoid and vanilloid systems exert opposite effects in several animal models of anxiety. Based on this evidence, this study investigated the involvement of TRPV1 receptors in two animal models of panic: the injection of the NMDA agonist dlPAG and the elevated T maze (ETM). The animals underwent stereotaxic surgery for implantation of the cannula guide into dlPAG and after a recovery period were subjected to behavioral tests. The results show that injection of NMDA (1.0 nmol/0.2 L) into dlPAG produced flight reactions characterized by increase in jumps and crossings and that this effect was abolished when animals were pretreated with capsazepine (TRPV1 receptor antagonist) at a dose of 1 nmol/ 0.2 L into dlPAG. When the rats were submitted to ETM, capsazepine (60 nmol/0.2 L) into dlPAG induced panicolityc-like effectcharacterized by an increased latency to reach the center of the maze when the animals were exposed to the open arm. This effect was blocked by pretreatment of CB1 antagonist, AM251 (100 pmol/0.2 L) into dlPAG, suggesting that this effect is dependent on cannabinoid activation. In conclusion, it appears that the vanilloid receptors modulate defensive responses mediated by dlPAG, possibly, facilitating glutamatergic neurotransmission